The issue of spelling errors in the books of Atraf ul Hadith Study of the book "al'afrad Walgharayib" By Imam Al-Daraqutni as a model: مسألة أخطاء الإملائیة فی کتب اطراف الحدیث دراسة کتاب الأفراد والغرائب نموذجا - Ahmed, Altaf; Sahibdad, Dr. Mufti Muhammad; Ahmed, Sajjad (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Arabic language is a very sensitive in a sense that a change in a letter or Harkat( Fath, Zamma and Kasra) can cause a huge difference in the meaning. If such errors occur in books of Atraf, it can cause multiple difficulties in reaching the exact Hadith. The book Al Garaib wal Afraad is no exception. There are many spelling mistakes in this book and there can be many reasons of it. The book consists of 6400 Afrad Ahadith; I have just conducted research from Musnad Muaaz Bin Jabl, Hadith number 4284 to 4592 around 308 Ahadith. From these Ahadith, I encountered 18 such Ahadith where such errors can be found. This research paper contains an introduction, three chapters and the conclusion. The first chapter deals with a short introduction of the book Al Garaib wal Afraad; while the second chapter presents a brief introduction of life of Imam Dar Qutni. The third chapter presents examples of spelling errors from the book. In conclusion, outcomes of the research have been provided. The research is a descriptive and empirical in its nature as it will give evidences from the book